Psychosocial Consequences of Intimate Partner Violence (IPV) Exposure in Maltreated Adolescents: Assessing More than IPV Occurrence - Garrido, Edward F. (2011)
The majority of research on the psychosocial impact of intimate partner violence (IPV) exposure for children has focused on IPV occurrence. The current study extended this research by examining three dimensions of IPV exposure: frequency, proximity, and severity, and tested whether these dimensions predicted variance in adolescents' psychosocial problems over-and-above that accounted for by IPV occurrence. Participants included 140 adolescents and their caregivers, who were recruited for an intervention involving maltreated youth placed in out-of-home care. After controlling for IPV occurrence, exposure to community violence, and severity of maltreatment, results indicated a positive association between the multidimensional IPV index and youth report of psychosocial problems. There was also a trend for a positive association between the IPV index and caregiver report of psychosocial problems for boys. The study's results are discussed in terms of their implications for prevention researchers and child welfare agencies.